Shared motifs: Body attachments in RL and SL. Issue 2 (31st August 2011) - Beloff, Laura
This article investigates real time and virtual body attachments that are created with a deliberately intense aesthetic and theatrical characteristic. These body attachments form the focus of wearable technology augmentations that are emerging in real life (RL) and avatar attachments that are created in Second Life® Metaverse (SL). The objective of the investigation reflects the motivations behind the designs and shared characteristics of the body attachments in RL and SL. The article looks into self as a performance (Goffman), appearance and clothing as systems of communication (Barthes), the element of style as a subcultural strategy (Hebdige) and the expression of irony as a chosen tactic for artistic work. Additionally, the article introduces RL body attachments by the artist Laura Beloff and SL body attachments by the SL designer Cutea Benelli, among a few other examples.